The Sibyl and her scribes : manuscripts and interpretation of the Latin Sibylla Tiburtina c. 1050-1500 /: manuscripts and interpretation of the Latin Sibylla Tiburtina c. 1050-1500. (2017) - Unknown
No abstract available